A randomized control trial on early open patient department-based assessment tool for prediction of neurological outcomes at the age of 1 month of life in asphyxiated neonates who underwent whole body cooling at tertiary care hospital in Southern Rajasthan - Sanadhya, Anuradha; Goyal, Suresh; Mehrotra, Juhi; Malvia, Sunny (International Journal of Contemporary Pediatrics, 2021)
Background: Therapeutic hypothermia (TH) is standard-of-care for infants with moderate to severe hypoxic ischemic encephalopathy (HIE) in developed countries. It should be implemented within 6 hours after delivery, and it has shown to significantly decrease the risk of brain injury in newborns exposed to perinatal hypoxemic ischemic insult with improved neurological outcomes. Objectives of the study were to assess early neurological outcome of neonates with moderate to severe birth asphyxia treated with TH. Methods: A randomized control trial was done in NICU of Balchikitsalaya, RNT medical college, Udaipur, on neonates with evidence of grade II/III HIE. We used phase changing material-FS 21, FS 29 to provide whole body hypothermia for 72 hours within 6 hours of birth and observed the babies for early neurological outcome. Results: A total of 60 neonates were enrolled in the study, 30 as cases, treated with therapeutic hypothermia and 30 as controls in normothermic environment. Neurological assessment was made on the basis of Thompson scoring and Ameil-Tison neurological assessment at term (ATNAT) at one month of age. We observed a better ATNAT score in TH group as compared to controls (p<0.05). Thompson score was significantly less in surviving neonates suggestive of better early neonatal outcome. Conclusions: Statistically significant data suggestive of better early neurological outcomes were seen in the cases treated with 72 hours of hypothermia. These babies not only had lesser Thompson scores, but also showed better tone, and Improved ATNAT scores at 1 month of age, making this study important as an early marker of neurological injury/morbidity in later life.